Heart rate variability analysis in sport: Utility, practical implementation and future perspectives - Makivic, B.; Bauer, P. (ASPETAR Sports Medicine Journal, 2015)
Heart rate variability (HRV) represents variations between consecutive heart beats (beat to beat or R-R interval) over time (Figure 1). This beat to beat variation in heart rhythm is considered normal and even desirable. Disappearance of variations between consecutive heart beats is a result of autonomic dysfunction which can be associated with neurological, cardiovascular and psychiatric disease states1. There is a large body of evidence reporting that higher variability of heart rhythm is associated with reduced mortality 2,3, improved quality of life4 and better physical fitness5. The most common use of HRV analysis is in risk prediction and prevention of heart failure6,7.